Partial mGlu5 Negative Allosteric Modulator M-5MPEP Demonstrates Antidepressant-Like Effects on Sleep Without Affecting Cognition or Quantitative EEG - Holter, Kimberly M.; Lekander, Alex D.; LaValley, Christina M.; Bedingham, Elizabeth G.; Pierce, Bethany E.; Sands, L. Paul; Lindsley, Craig W.; Jones, Carrie K.; Gould, Robert W. (Frontiers in Neuroscience, 2021)
Selective negative allosteric modulators (NAMs) targeting the metabotropic glutamate receptor subtype 5 (mGlu5) demonstrate anxiolytic-like and antidepressant-like effects yet concern regarding adverse effect liability remains. Functional coupling of mGlu5 with ionotropic N-methyl-D-aspartate receptors (NMDARs) represents a potential mechanism through which full inhibition leads to adverse effects, as NMDAR inhibition can induce cognitive impairments and psychotomimetic-like effects. Recent development of “partial” mGlu5 NAMs, characterized by submaximal but saturable levels of blockade, may represent a novel development approach to broaden the therapeutic index of mGlu5 NAMs. This study compared the partial mGlu5 NAM, M-5MPEP, with the full mGlu5 NAM, VU0424238 on sleep, cognition and brain function alone and in combination with a subthreshold dose of the NMDAR antagonist, MK-801, using a paired-associates learning (PAL) cognition task and electroencephalography (EEG) in rats. M-5MPEP and VU0424238 decreased rapid eye movement (REM) sleep and increased REM sleep latency, both putative biomarkers of antidepressant-like activity. Neither compound alone affected accuracy, but 30 mg/kg VU0424238 combined with MK-801 decreased accuracy on the PAL task. Using quantitative EEG, VU0424238, but not M-5MPEP, prolonged arousal-related elevations in high gamma power, and, in combination, VU0424238 potentiated effects of MK-801 on high gamma power. Together, these studies further support a functional interaction between mGlu5 and NMDARs that may correspond with cognitive impairments. Present data support further development of partial mGlu5 NAMs given their potentially broader therapeutic index than full mGlu5 NAMs and use of EEG as a translational biomarker to titrate doses aligning with therapeutic versus adverse effects.